2015
DOI: 10.1007/s12160-014-9683-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Coach Communication About Concussion Safety in US Collegiate Sport

Abstract: These results serve as a starting point for the design of coach-targeted interventions that encourage communication about health and safety with athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 65 publications
(76 reference statements)
1
38
0
Order By: Relevance
“…There has been a growing focus on the role coaches can play in translating information about concussion safety to athletes and in creating a culture of risk or safety with respect to concussions (Baugh, Kroshus, Daneshvar & Stern, 2014; Chrisman et al, 2014; Covassin et al, 2012; Kroshus et al, 2015; Rivara et al, 2014), with a frequent subtext that there is room for improvement. For example, collegiate football players who perceived less support from their coach for appropriate concussion symptom reporting were more likely to continue play while symptomatic (Baugh, Kroshus, Daneshvar & Stern, 2014); however, there was no indication of whether this appraisal of what the coach wanted them to do was based on pressure being communicated directly at them.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a growing focus on the role coaches can play in translating information about concussion safety to athletes and in creating a culture of risk or safety with respect to concussions (Baugh, Kroshus, Daneshvar & Stern, 2014; Chrisman et al, 2014; Covassin et al, 2012; Kroshus et al, 2015; Rivara et al, 2014), with a frequent subtext that there is room for improvement. For example, collegiate football players who perceived less support from their coach for appropriate concussion symptom reporting were more likely to continue play while symptomatic (Baugh, Kroshus, Daneshvar & Stern, 2014); however, there was no indication of whether this appraisal of what the coach wanted them to do was based on pressure being communicated directly at them.…”
Section: Discussionmentioning
confidence: 99%
“…The approach to SRC prevention should be multifactorial and encompass more than simply providing an education sheet and a video for athletes and coaches. Measures of the effectiveness of concussion policies and programs should extend beyond knowledge 63,78 Encourage teammates in concussion safety and concussion disclosure 83 During preseason, AT holds parent-team meetings to educate about concussion, review appropriate policies, and discuss postinjury management scenarios AT provides postinjury anticipatory guidance to patients and families throughout recovery course Intrapersonal Educate athletes and provide opportunities for experiential and observational learning 93 Address attitudes about concussion disclosure 13,89 Encourage and support concussion disclosure 63 Correct misperceived concussion-related norms 79,80 Educate athletes about appropriate sport skills aimed at keeping head out of play and following rules 43 Ensure that concussion education being provided to athletes has been evaluated and demonstrated effectiveness in changing at least knowledge but ideally other relevant factors (eg, attitudes, norms, and reporting intention) Remind athletes about importance of concussion safety throughout season…”
Section: Discussionmentioning
confidence: 99%
“…In fact, evidence from collegiate coaches suggests that those who have greater SRC knowledge are not more likely to communicate with athletes in support of SRC safety. 79 Understanding the coach-level factors that predict support of reporting is an important direction for future research and can inform the development of effective coach education to encourage this behavior. Athletic trainers should discuss the importance of supportive communication with coaches.…”
Section: Interpersonal Levelmentioning
confidence: 99%
“…An athlete’s hesitation to report an injury has been linked to a variety of factors, such as fear of losing playing time, competitive pressure to win the game, reluctance to appear weak in front of coaches and teammates, or improper understanding of injuries 21 . Sociological relationships that the player engages in are key factors in shaping perception of injury, and one of the most important is the athlete’s relationship with their coaches 22 . Sports medicine research has indicated that an athlete’s likelihood of reporting an injury, particularly serious injuries such as concussions, depends significantly on the coaching outlook and the value that the coaches place on injury prevention and rehabilitation 6,22 .…”
Section: Coaches’ Philosophymentioning
confidence: 99%
“…Sociological relationships that the player engages in are key factors in shaping perception of injury, and one of the most important is the athlete’s relationship with their coaches 22 . Sports medicine research has indicated that an athlete’s likelihood of reporting an injury, particularly serious injuries such as concussions, depends significantly on the coaching outlook and the value that the coaches place on injury prevention and rehabilitation 6,22 . Thereby, a coach’s principles can play a large role in their athlete’s well-being, and the creation of a team that values injury prevention; management may start at the level of the coach.…”
Section: Coaches’ Philosophymentioning
confidence: 99%